Effect of Operating Conditions on Separation of H2S from Biogas Using a Chemical Assisted PDMS Membrane Process - ÇALLI, BARIŞ (SPRINGER, 2018)
Hydrogen sulfide (H2S) is an undesirable impurity that has to be removed from biogas to avoid the corrosion of co-generation units. In the present study, we evaluated the potential of a gas-liquid membrane contactor process for selective removal of H2S from biogas. The effects of biogas retention time (GRT), membrane thickness and liquid absorbent pH were investigated. A dilute sodium hydroxide solution was used as absorbent. The results revealed that H2S removal efficiency (RE) improved with increasing GRT and absorbent pH, and decreased with increasing membrane thickness. When GRT reduced from 19 to 3.4min, the RE of H2S and CO2 decreased by over 2.5 and 5.2 times, respectively. In contrast, a higher desulfurization selectivity was observed with lower GRT and thicker membranes. The CH4 content of the treated biogas increased along with increasing GRT and was enriched from 60% to a maximum of 87% with only 4.68% loss. The SEM-EDS analysis confirmed the deposition of inorganics such as Ca, Mg, S and Si on the membrane surface. However, any membrane clogging and fouling problem was not observed. In summary, the novel gas-liquid polydimethylsiloxane membrane contactor tested in this study has performed well in selective removal of H2S from biogas and is expected to be a promising alternative to conventional desulfurization processes.
Keywords: Biogas; Desulfurization; Inorganics deposition; CH4 content; Membrane separation; HYDROGEN-SULFIDE; GAS-ABSORPTION; CO2 SEPARATION; REMOVAL; CONTACTORS; PURIFICATION; BIOREACTOR; RESISTANCE; DIGESTION; CAPTURE